Mechanisms of attenuation of clot formation and acute thromboembolism by syringic acid in mice - Jun-Hui Choi; Seung Kim (Journal of Functional Foods, 2018)
Several in vitro studies have proposed syringic acid as a benzoic acid derivative found in plant foods, which can reduces collagen-stimulated platelet aggregation. Nonetheless, to date, there are no reports elucidating the role of syringic acid in platelet activation and thrombosis. Syringic acid inhibited clot formation and procoagulant protease activity and induced blood clot degradation. Syringic acid decreased the expression of density-enhanced phosphatase-1 (DEP-1)/protein tyrosine phosphatase-1B (PTP1B)/αIIbβ3, as well as the phosphorylation of kinases in collagen/epinephrine-stimulated platelets both in vitro and in vivo. Moreover, syringic acid inhibited the secretion of granule constituents, clot retraction, and FeCl3-induced vascular occlusion of the carotid artery. Syringic acid (up to 100 μM) did not show any effect on the viability of RAW 264.7 cells. Our findings demonstrate that syringic acid attenuate the development of thrombosis and thromboembolism by inhibiting fibrin clot formation, coagulant factors, and platelet stimulation through DEP-1/PTP1B/αIIbβ3/kinases.